Conformational transitions monitored for single molecules in solution. - Edman, L (1996)
Phenomena that can be observed for a large number of molecules may not be understood if it is not possible to observe the events on the single-molecule level. We measured the fluorescence lifetimes of individual tetramethylrhodamine molecules, linked to an 18-mer deoxyribonucleotide sequence specific for M13 DNA, by time-resolved, single-photon counting in a confocal fluorescence microscope during Brownian motion in solution. When many molecules were observed, a biexponential fluorescence decay was observed with equal amplitudes. However, on the single-molecule level, the fraction of one of the amplitudes spanned from 0 to unity for a collection of single-molecule detections. Further analysis by fluorescence correlation spectroscopy made on many molecules revealed a process that obeys a stretched exponential relaxation law. These facts, combined with previous evidence of the quenching effect of guanosine on rhodamines, indicate that the tetramethylrhodamine molecule senses conformational transitions as it associates and dissociates to a guanosine-rich area. Thus, our results reveal conformational transitions in a single molecule in solution under conditions that are relevant for biological processes.